Penguatan Motivasi Belajar Matematika melalui Strategi Siswa Sukses (3S) bagi siswa SMP di Kabupaten Cirebon - Rifqi Hidayat; Muhammad Wildan Alfariq; Aina Refani (SIKAP : Jurnal Sinar Inovasi Kajian Pemberdayaan Masyarakat, 2025)
Learning motivation is an important factor that influences students’ success in mathematics learning. However, many students still have low motivation to learn mathematics because they perceive the subject as difficult and less interesting. Therefore, an appropriate strategy is needed to improve students’ learning motivation. This community service activity aimed to strengthen students’ motivation in learning mathematics through the implementation of the Successful Student Strategy (3S) for junior high school students in Cirebon Regency. The method used in this activity was a participatory mentoring approach consisting of several stages, namely socialization, training, learning practice, and reflection. The evaluation of the activity was conducted using a mathematics learning motivation questionnaire based on a Likert scale administered before and after the program, supported by observations of students’ learning activities during the implementation. The results showed that the implementation of the Successful Student Strategy (3S) was able to increase students’ motivation in learning mathematics. This improvement was indicated by the increase in the average motivation score from 3.02 before the activity to 4.10 after the activity. In addition, students also demonstrated higher participation in learning activities, greater confidence in solving mathematical problems, and increased willingness to express their opinions during discussions. These findings indicate that the Successful Student Strategy (3S) can serve as an effective alternative approach to enhance students’ motivation in mathematics learning. This community service activity is expected to contribute to improving the quality of mathematics learning in schools by strengthening students’ motivation and promoting more effective learning strategies.